Genetic diversity of laboratory strains and implications for research: The case of Aedes aegypti. - Andrea Gloria-Soria; John Soghigian; David Kellner; Jeffrey R Powell (Public Library of Science (PLoS), 2019)
The yellow fever mosquito (Aedes aegypti), is the primary vector of dengue, Zika, and chikungunya fever, among other arboviral diseases. It is also a popular laboratory model in vector biology due to its ease of rearing and manipulation in the lab. Established laboratory strains have been used worldwide in thousands of studies for decades. Laboratory evolution of reference strains and contamination among strains are potential severe problems that could dramatically change experimental outcomes and thus is a concern in vector biology. We analyzed laboratory and field colonies of Ae. aegypti and an Ae. aegypti-derived cell line (Aag2) using 12 microsatellites and ~20,000 SNPs to determine the extent of divergence among laboratory strains and relationships to their wild relatives. We found that 1) laboratory populations are less genetically variable than their field counterparts; 2) colonies bearing the same name obtained from different laboratories may be highly divergent; 3) present genetic composition of the LVP strain used as the genome reference is incompatible with its presumed origin; 4) we document changes in two wild caught colonies over ~16 generations of colonization; and 5) the Aag2 Ae. aegypti cell line has experienced minimal genetic changes within and across laboratories. These results illustrate the degree of variability within and among strains of Ae. aegypti, with implications for cross-study comparisons, and highlight the need of a common mosquito repository and the implementation of strain validation tools.